Systematic review to the genus Liothorax (Coleoptera: Scarabaeoidea: Scarabaeidae: Aphodiinae) - Dellacasa, Marco; Gordon, Robert D.; Dellacasa, Giovanni (Zootaxa, 2007)
The genus Liothorax Motschulsky, 1859 is herein reviewed and considered to consist of 10 species. A key to species and diagnoses of each species are given to facilitate identification. Based on the study of type material, Aphodius bytinskisalzi Petrovitz, 1971 is placed as a junior synonym of A. isikdagensis Balthasar, 1952 and Aphodius nigroclavus Hinton, 1934 is placed as a junior synonym of A. levatus Schmidt, 1907. A lectotype is designated for A. levatus Schmidt, 1907. The following new combinations are formulated: Liothorax alternatus (Horn, 1870), Liothorax consociatus (Horn, 1887), Liothorax isikdagensis (Balthasar, 1952), Liothorax kraatzi (Harold, 1868), Liothorax levatus (Schmidt, 1907), Liothorax rusakovi (Gusakov, 2004), and Liothorax subaeneus (LeConte, 1857).